Synthesis, Characterization, In-Silico Drug Discovery And In-Vitro Biological Evaluation Of Morpholinium 2, 6-Pyridine Dicarboxylate (Journal of Pharmaceutical Negative Results, 2023)
The general composition of morpholinium 2, 6-pyridine dicarboxylates are (C4H10NO)Hdip (DM11), (C4H10NO)2dip.H2O (DM12) and (C4H10NO)Hdip.H2dip (DM21), on treatment with dipicolinic acid (H2dip), the aqueous solution of morpholine yields morpholinium 2,6-pyridine dicarboxylates. The structural arrangement of the synthesized compound was confirmed by spectroscopic techniques such as FT-IR, UV, 1H NMR and 13C NMR. Infrared spectra of the salts revealed the N–H extending vibration frequencies of the nonpartisan morpholine particle in the locale 3200 - 3500 cm–1. The absorption, distribution, metabolism and excretion (ADMET) properties and DFT tests were performed for the examples DM11, DM12 and DM21. The in-vitro calming movement was done for DM11, DM12, DM21 and Standard (diclofenac), where DM12 is taken as the norm. Atomic docking was performed for both mixtures with cyclooxygenase 1. Henceforth, our point is to discover the absorption, distribution, metabolism, excretion and toxicity (ADMET) in-silico model, in-vitro mitigating action and sub-atomic docking reads for morpholinium-inferred compounds.